A2.17 Detection of autoantigen-specific CD4+ T cells associated with systemic lupus erythematosus. (24th February 2016) - Abdirama, D; Enghard, P; Tesch, S; Radbruch, A; Burmester, GR; Riemekasten, G
Abstract : Background and objectives: Systemic lupus erythematosus (SLE) is a chronic systemic autoimmune disease characterised by the development of autoantibodies directed to nuclear components such as SmD1, RNP70, Histone, Ro and La resulting in the loss of tolerance towards these autoantigens. Autoantigen-specific CD4 + T cells are implicated in SLE, but little is known about their frequency in health and disease. To determine frequency of CD4 + T cells specific for SmD1, RNP70, Histone, Ro and La, we generated libraries of polyclonally expanded CD4 + T cells from SLE patients and healthy individuals. In addition, we investigated the accumulation of autoantigen-specific CD4 + T cells in inflamed organ eg, the kidneys of active SLE patients with lupus nephritis. Materials and methods: 200.000 CD4 + T cells isolated from the blood and urine of active SLE patients with lupus nephritis (n = 4) or isolated only from the blood of inactive SLE patients (n = 4) and healthy individuals (n = 4) were seeded in multiple micro-cultures containing irradiated feeder cells, PHA and IL-2 for two weeks. Expanded CD4 + T cells were tested for their capacity to proliferate in response to SmD1, RNP70, Histone, Ro and La in the presence of autologous antigen-presenting cells. After 3 days, proliferation was measured after 16-hours pulse with [3H]-thymidine. Results: Among 200.000 cells, autoantigen-specific CD4 + T cells are more detectable in active SLE patients in comparison to inactive SLE patients. In healthy individuals, the cells are not or less detectable except in one donor. Autoantigen-specific CD4 + T cells are more enriched in urine than in the peripheral blood of active SLE patients with lupus nephritis. Micro-cultures containing autoantigen-specific CD4 + T cells show a sizeable portion of T cells up-regulated CD154 and IFN-g after 6 h stimulation with autoantigen. Conclusions: Our data suggest that SLE-associated autoantigen-specific CD4 + T cells are circulating in the periphery of SLE patients with active disease at higher frequency in comparison to inactive SLE patients and healthy individuals. An accumulation of autoantigen-specific CD4 + T cells was observed in the inflamed kidneys, suggesting their potential role in the local inflammation.